Bile acid-based bio micro/nanotechnologies; biocompatibility studies - Kovacevic, Božica (Curtin University, 2024)
Biocompatible hydrogels are versatile biomaterials utilized for micro/nano-encapsulation, injectable gels, and bioprinted scaffolds, facilitating drug and cell delivery. Bile acids, known permeation enhancers, self-assemble into micelles, augmenting drug absorption through membrane interactions. They enhance biomaterial durability and reduce inflammation, activating various receptors for immunomodulation. Incorporating bile acids into hydrogel matrices improves rheological properties and biocompatibility, with smart thermoresponsive nanogels exhibiting promise as inner ear drug delivery vehicles.